Analysis of Electric Propulsion Performance on Submersible with Motor DC, Supply Power 10260AH at Voltage 115VDC - Indra Ranu Kusuma; Sardono Sarwito; Ristita Angarini Widya Ayu Irawati (International Journal of Marine Engineering Innovation and Research, 2017)
Electric propulsion is the ship system using propulsion motor to replace performance of main engine. The application of diesel engine as propulsion system have some problems and weaknesses such as diesel engine unability to operate when submersible vessel is operating under sea. To overcome that problems in submersible vessel, alternative solution of ship propulsion is required. DC Motor can be used as this alternative solution. Submersible vessel use electric propulsion system with DC Motor because DC Motor has advantages of easy rotation setting and does not cause noise when submersible vessel is diving. This bachelor thesis will study the application of DC Motor as an electric propulsion system on submersible vessel with length 59,57 m in series and parallel circuit by simulation using MATLAB software. The simulation data obtained are rotation and torque of DC Motor. From these simulation, it can be concluded that parallel circuit rotation is greater than series circuit rotation. It caused the greater speed and lower power in parallel circuit.